2000
DOI: 10.3109/02770900009055456
|View full text |Cite
|
Sign up to set email alerts
|

Heat-KilledMycobacterium bovis-Bacillus Calmette Guerin-Suppressed Total Serum IgE Response in Ovalbumin-Sensitized Newborn Mice

Abstract: To determine the impact of bacillus Calmette Guerin (BCG) vaccination on IgE production in ovalbumin (OVA)-sensitized newborn mice, four groups (I, II, III, IV) of BALB/c mice were immunized on the first day of life with live BCG, killed BCG, BCG diluent, and saline, respectively. No injection was applied to mice in group V (control). All mice except group V were sensitized and challenged with OVA in the fourth and sixth weeks, respectively, and serum total IgE levels were determined at 8 weeks, 2 weeks after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
1
17
2
Order By: Relevance
“…These results are in agreement with the results from other studies (30,33,36) and indicated that OVA-specific IgE, IFN-␥, IL-4, and IL-10 might not be responsible for changes of asthmatic inflammation and AHR caused by BCG and RSV interference in our mouse model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with the results from other studies (30,33,36) and indicated that OVA-specific IgE, IFN-␥, IL-4, and IL-10 might not be responsible for changes of asthmatic inflammation and AHR caused by BCG and RSV interference in our mouse model.…”
Section: Discussionsupporting
confidence: 83%
“…Because a survey from Japan reported that skin test reactivity to tuberculin was shown to inversely correlate with the likelihood of having asthma (4), BCG has been studied as an anti-asthma vaccine in an attempt to verify the "hygiene hypothesis" in animals and in humans. Most of the animal studies focused on the impact of BCG on adult mice, whereas several studies used neonatal mice as a model to study heat-killed BCG by direct intranasal BCG administration (29,30). In this study, we demonstrated that live BCG inoculated in neonatal mice by subcutaneous administration was capable of suppressing the development of OVA-induced airway eosinophilia, AHR, and histologic inflammation.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to us, others have demonstrated a suppressive effect on various parameters of allergic inflammation in mouse models after mycobacteria pretreatment (4,5,8,9). However, except for one report from the work of Wang and Rook (7), there is no information as to the potential for these Ags in attenuating a preexisting allergic state.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have suggested that the Bacillus ChalmetteGuerin (BCG) vaccine may be useful as an adjuvant for the treatment of allergic diseases [23][24][25][26][27]. Yoneyama et al demonstrated that successful BCG vaccination inhibits the development of AD and asthma in children [27].…”
Section: Discussionmentioning
confidence: 99%